Surfing the Capital Waves: A sector-level examination of surges in FDI inflows - Salvatore Dell'Erba; Dennis Reinhardt (Swiss National Bank, Study Center Gerzensee, 2011)
We examine episodes of large gross FDI inflows - surges - at the sectoral level between 1994 and 2009 for 95 emerging-market and industrial countries. We find that surges in the primary and manufacturing sectors are less cyclical and associated with lower macroeconomic volatility than surges in the business and finance sectors. The likely explanation for this result seems to be the expansion of credit associated with these flows. Turning to the determinants of surges, we find that global and contagion factors have a stronger effect in the services than the manufacturing sector; surges in financial sector FDI are particularly contagious in emerging market countries. With regard to domestic factors, we find that (i) high public debt reduces the likelihood of experiencing FDI surges in the manufacturing and trade/transport sector, that (ii) high growth pulls in FDI in the manufacturing sector and that (iii) privatization is strongly associated with FDI surges in the manufacturing and financial sector. Finally, we document a role for capital controls: they tend to increase the likelihood of FDI surges in the manufacturing, other services, and financial sector.
Keywords: F21; F32; 330; Foreign Direct Investment; Surges; Capital Flow Determinants; Sectoral Level; Auslandsinvestition; Kapitalimport; Branche; Vergleich; Welt